The Rate of Knowledge and Practice of Medical Residents of Shiraz Medical School in Regard to Evidencebased Medicine - Mitra Amini; Mohammad Mehdi Sagheb; Mohsen Moghadami; Sedighe Shayegh (Kerman University of Medical Sciences, 2007)
Background & Objective: Evidencebased medicine (EBM) is defined as the application of the best research evidence in making decisions in the management of the individual patient EBM due to its importance has obtained great consideration in recent years This study was designed to determine the knowledge of Medical residents in Shiraz School of Medicine about EBM and the application of it by them Methods : In this crosssectional study performed in 2006 71 residents of Shiraz School of Medicine were studied by using a questionnaire The validity of the questionnaire was approved by getting experts opinions and internal consistency reliability was determined in a pilot study Results : In whole 939% of residents had positive attitudes toward EBM but 803% of them reported that they had not passed any formal education in this field From all participants 85% have access to internet but more than 70% of them were not aware of EBM resources and 609% of them mentioned that for the management of their patients during the previous year they had used Medline or other search engines less than 10 times Conclusion : According to the obtained results in spite of positive attitude toward EBM and internet access residents have not yet integrated the use of EBM with their professional practice widely and also they are not familiar with specific EBM Sites This may be due to the lack of education in the field of EBM Because of the important role of Medical residents in making clinical decisions and also their role in training Medical students inclusion of EBM training courses in their educational program is highly necessary